Pseudo-plaque reduction neutralization test (PPRNT) for the measurement of neutralizing antibodies to Crimean-Congo hemorrhagic fever virus - Canakoglu, Nurettin; Berber, Engin; Ertek, Mustafa; Yoruk, Mustafa D.; Tonbak, Sukru; Bolat, Yusuf; Ozdarendeli, Aykut (Bmc, 2013)
Background: Crimean-Congo hemorrhagic fever virus (CCHFV) is a tick-borne virus of the genus Nairovirus family Bunyaviridae, which are enveloped viruses containing tripartite, negative polarity, single-stranded RNA. CCHF is characterized by high case mortality, occurring in Asia, Africa, the Middle East and Europe. Currently, there are no specific treatments or licensed vaccines available for CCHFV. Recently, two research groups have found adult mice with defective interferon responses allowed to lethal CCHFV infection. These mouse models could provide invaluable information for further studies. Efforts to develop a vaccine against CCHFV are being made. To determine the efficacy of vaccine candidates it is important to conduct serological studies that can accurately measure levels of protective antibodies. In the present study, a pseudo-plaque reduction neutralization test (PPRNT) based on enzyme-catalyzed color development of infected cells probed with anti-CCHFV antibodies was used to measure neutralization antibody of CCHFV. Methods: Sixty-nine human serum samples (20 acute and 49 convalescent) were tested. The presence of CCHFV antibodies was determined and confirmed by a commercial ELISA kit. CCHFV RNA was determined by RT-PCR. All the samples were analyzed by PPRNT and fluorescent focus reduction neutralization test (FFRNT) to measure of CCHFV-neutralizing antibodies. Results: Pseudo-plaque reduction neutralization test showed a high sensitivity (98%), specificity (100%) and agreement (96,6%) in qualitative comparison with those of the FFRNT. There was a high correlation between the titers obtained in PPRNT and FFRNT (R2 = 0.92). The inter-and intra-assay variation of PPRNT revealed good reproducibility and positive cut-off of PPRNT was defined as 1: 4 by the geometric mean titers for the individual samples distributed. Conclusion: The pseudo-plaque reduction neutralization test described in this study is a fast, reproducible and sensitive method for the measurement of CCHF neutralizing antibodies. This novel assay could serve as useful tools for CCHF research in epidemiology, vaccine development and other studies of immunity. It also provides an alternative to PRNT when viruses with no or poor CPE in cell culture.
Keywords: CCHF; CCHF-neutralizing antibodies; Pseudo-plaque reduction neutralization test; Fluorescent focus reduction neutralization test